Micro-components of aggregate wage dynamics - Antti Kauhanen; Mika Maliranta (The Research Institute of the Finnish Economy (ETLA), 2012)
We propose an approach for measuring and analyzing the dynamics of standard aggregate wage growth of macro statistics with micro-data. Our method decomposes aggregate wage growth to the wage growth of job stayers and to various terms related to job and worker restructuring. This method produces explicit expressions with clear interpretations for the various restructuring components and therefore opens new opportunities for a deeper analysis of various micro-level mechanisms and their cyclicality. The methodology also allows us to study many topics simultaneously that have previously been studied in isolation. Using comprehensive longitudinal employer-employee data over an extended period of time, we study how job and worker restructuring influences aggregate wage growth and its cyclicality. We show that wage formation is significantly more flexible than suggested by the aggregate numbers, and we identify the microlevel mechanisms that explain the greater flexibility. This version: December 7, 2012
Keywords: 330